Concatenated RS-convolutional codes for MIMO-OFDM over multipath fading channel - Hussain, Ghasan Ali (2013)
The enormous developments through recent years in the wireless communications applications have led to important needs for increasing the data bandwidth and channel reliability (the probability of correct reception at the receiver) which are required to support several multimedia applications. Orthogonal Frequency Division Multiplexing (OFDM) has become the common method for services that need high data rate and robust to the inter-symbol interference (ISI). On the other hand, high data rate transmission needs more bandwidth. This problem gives a great motivation to use Multiple Input Multiple Output (MIMO) technique as a solution to increase the spectral efficiency. Therefore, the combination of OFDM with MIMO systems will allow higher data throughput while increasing the bandwidth efficiency at the same time. However,the channel coding technique is still required in MIMO-OFDM system in order to improve error performance by protecting the data transmission and decreasing the Bit Error Rate (BER) over fading and noisy channel. Therefore, this thesis proposes a concatenated Reed-Solomon\Convolutional code for MIMO-OFDM system as a channel coding technique, so that the bandwidth efficiency and the channel reliability can be increased. The performance of MIMO-OFDM using concatenated Reed-Solomon and Convolutional Codes is investigated over Rayleigh fading channel with Additive White Gaussian Noise (AWGN), and Rician fading channel with AWGN. The simulation works have been carried out using MATLAB software. The channel reliability improvements are performed by the curve of Bit Error Rate (BER) against Signal-to- Noise Ratio (SNR). The performance of MIMO-OFDM system with concatenated code has also been compared with other possible concatenated systems over Rayleigh and Rician fading channel. Using the proposed system, a coding gain up to 16dB at 10-3 of BER has been obtained over Rayleigh fading channel with AWGN, while 11dB of coding gain at 10-3 of BER has been achieved over Rician fading channel with AWGN, compared to uncoded MIMO-OFDM system also it performs better than other concatenated MIMO-OFDM systems. The results show that the proposed code rate is performed better than other code rates with MIMO-OFDM system over both of Rayleigh and Rician fading channel with AWGN. Lastly, the burst error has been analyzed in our proposed system for both of interleaving process and Reed-Solomon Codes.